Endogenous Growth, Monetary Shocks and Nominal Rigidities - Barbara Annicchiarico; Alessandra Pelloni; Lorenza Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
We introduce endogenous growth in an otherwise standard NK model with staggered prices and wages. Some results follow: (i) monetary volatility negatively affects long-run growth; (ii) the relation between nominal volatility and growth depends on the persistence of the nominal shocks and on the Taylor rule considered; (iii) a Taylor rule with smoothing increases the negative effect of nominal volatility on mean growth.
Keywords: E32; E52; O42; 330; Growth; volatility; business cycle; monetary policy